Specialized pediatric palliative care in Italy: where are we going? The Palliped 2022–2023 study - Franca Benini; Anna Mercante; Sara Di Nunzio; Simonetta Papa; the PalliPed 2022-2023 Working Group (Italian Journal of Pediatrics)
Abstract Background The PalliPed project is a nationwide, observational, cross-sectional study designed with the aim of providing a constantly updated national database for the census and monitoring of specialized pediatric palliative care (PPC) activities in Italy. This paper presents the results of the first monitoring phase of the PalliPed project, which was developed through the PalliPed 2022–2023 study, to update current knowledge on the provision of specialized PPC services in Italy. Methods Italian specialized PPC centers/facilities were invited to participate and asked to complete a self-reporting, ad-hoc, online survey regarding their clinical activity in 2022–2023, in the revision of the data initially collected in the first PalliPed study of 2021. Results 18 specialized PPC centers/facilities from 14 Italian regions and two autonomous provinces participated; 13 were identified as regional referral centers (72.2%), with the acquisition of three new centers in comparison to 2021. Full coverage of the regional territory was reported by 54% of them, compared with 45% in 2021, while a 24/7 service was offered by 23%, compared with 27% in 2021. Eight of 13 referral centers (61%) had a dedicated team, compared with 91% in 2021. Also, an overall increase in the number of followed patients was observed, rising from 1,209 (2019) to 2,734 (2023). In line with previous data, most PPC healthcare providers were nurses (n = 181) and physicians (n = 89), with an overall increased number of PPC providers from 2021. Conclusions The nationwide PalliPed project established the first comprehensive overview and monitoring of the state of specialized PPC in Italy. Data reported within the PalliPed 2022–2023 monitoring study suggest a general improving trend in the availability of the specialized PPC service in Italy, compared with data collected in 2021. At the same time, the need for a greater effort to provide better care models and resources for specialized PPC remains, especially considering that the number of children needing PPC is constantly increasing.